Integrative Review of Workplace Health Promotion in the Business Process Outsourcing Industry: Focus on the Philippines - Cristela Mae C. Candelario; Ma Khristine A. Fullante; Warren Kemuel M. Pan; Ernesto R. Gregorio, Jr (Elsevier, 2024)
Objective: The Business Process Outsourcing (BPO) industry in the Philippines has experienced substantial growth, making a significant contribution to the country's economy. However, concerns about work-related health and safety issues have emerged, necessitating effective workplace health promotion strategies for BPO employees. Study design: An integrative review of relevant literature was conducted to explore workplace health promotion in the BPO sector. Methods: The search included quantitative, qualitative, and mixed-method studies, pertinent laws, policies, news articles, and reports published between 2000 and 2022. The scope was intentionally broad to encompass a diverse range of relevant evidence related to workplace health in this field. Articles published both in the English and Filipino languages were considered. Results: Findings revealed that BPO workers face risks related to physical and psychological stress, sleep disturbances, and occupational diseases owing to the unique challenges inherent to the nature of their jobs. While there are existing occupational health and labor laws, compliance among BPO companies remains a problem, and only a few organizations offer comprehensive wellness programs. Building upon the available evidence, a conceptual framework was developed to provide guidance for enhancing workplace health promotion initiatives specifically designed for BPOs in the country. Conclusion: Workplace health promotion is vital to warrant the health and safety of BPO workers. This study offers evidence-based recommendations for implementing effective well-being strategies, highlighting the importance of collaboration among employers, employees, and society to prioritize employee health in the workplace.